A Bump in the Road: How the Hostile AML Microenvironment Affects CAR T Cell Therapy - Epperly, Rebecca; Gottschalk, Stephen; Velasquez, M. Paulina (Frontiers in Oncology, 2020)
Chimeric antigen receptor (CAR) T cells targeting CD19 have been successful treating patients with relapsed/refractory B cell acute lymphoblastic leukemia (ALL) and B cell lymphomas. However, relapse after CAR T cell therapy is still a challenge. In addition, preclinical and early clinical studies targeting acute myeloid leukemia (AML) have not been as successful. This can be attributed in part to the presence of an AML microenvironment that has a dampening effect on the antitumor activity of CAR T cells. The AML microenvironment includes cellular interactions, soluble environmental factors, and structural components. Suppressive immune cells including myeloid derived suppressor cells and regulatory T cells are known to inhibit T cell function. Environmental factors contributing to T cell exhaustion, including immune checkpoints, anti-inflammatory cytokines, chemokines, and metabolic alterations, impact T cell activity, persistence, and localization. Lastly, structural factors of the bone marrow niche, secondary lymphoid organs, and extramedullary sites provide opportunities for CAR T cell evasion by AML blasts, contributing to treatment resistance and relapse. In this review we discuss the effect of the AML microenvironment on CAR T cell function. We highlight opportunities to enhance CAR T cell efficacy for AML through manipulating, targeting, and evading the anti-inflammatory leukemic microenvironment.